P256 Clinical sequelae of tuberculosis in children attending a single UK centre: An 11 year retrospective study. (12th November 2015) - Bhowmik, S; Nicol, S; Bell, C; Murray, C; Child, F
Abstract : Introduction: Although public health outcomes in tuberculosis (TB) are widely reported in the literature, there is little information on clinically important sequelae particularly in children. The aim of this study was to collect clinical outcome data on a cohort of children treated for TB in a tertiary children's hospital in the UK. Method: We performed a retrospective study of all children attending our centre aged <16 years who started treatment for TB disease between January 2003 and December 2013. Patients with latent TB were excluded. Children were divided into 2 groups: symptoms (suggestive of TB) or screening (new entrants and TB contacts) depending on their clinical presentation. Information about symptoms, comorbidities, diagnostic tests, treatment, side effects and clinical outcomes (end of treatment) was collected from medical records and enhanced TB surveillance reports. Results: 209 patient episodes in 205 children were identified (4 retreated ≥6 months after initial treatment); 96(47%) male; mean age 8.6 years (range 0.1–15.8); 40% Asian, 32% Black African, 19% White. Following WHO guidelines 49(23.4%) were definite (culture positive), 152(72.7%) probable and 8(3.8%) possible cases. 92(44%) presented with symptoms, 117(56%) through screening (111 contacts, 6 new entrants). Site of disease was pulmonary in 53%, hilar lymphadenopathy in 25%, military in 3%, central nervous system in 5% and other in 14%. Drug resistance was unusual (single 4%; multi 2%). All were HIV negative. The majority received quadruple therapy (84%), 27(13%) triple and 7(3%) other TB-drug regimes. Clinical outcomes were determined for 196 patients (see Table 1 ). All 14(7%) with adverse outcomes (including 1 death) presented with symptoms (p < 0.001). Samples for culture were obtained in 118 (74(80%) symptomatic; 44(38%) screened). Positive cultures were significantly more common in the symptomatic group (64%) compared with the screened group (4.5%; p < 0.001) and in those with an adverse outcome (86%) compared with good outcome (36%; p = 0.002). Conclusion: TB is not a benign disease in children. This study shows that clinical outcomes are significantly worse in those who present with symptoms compared with those identified through screening and reminds us of the importance of identifying children at risk of TB infection early.